(untitled) (Research, Society and Development, 2020)
Objective: map the concept of health vulnerability in the field of public health. Method: This is a scoping review that used the search equation vulnerability AND health in five databases. Eligibility criteria were the term ’vulnerability’ in the title and explicitly defined the concept. No year or language limits were applied, resulting in 101 articles for analysis. Results: Articles were found from 2002 and the concept was further discussed after 2010. From 2002 to 2010, qualitative studies were more present and then the quantitative ones stood out. The concept has worldwide coverage, especially Brazil; addressed more infectious diseases and primary care. Conclusion: the concept is discussed worldwide under traditional epidemiological aspects in the field of Collective Health, but there is a transition.